2021
DOI: 10.1007/s00500-021-05579-7
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning in recycling business: an investigation of its practicality, benefits and future trends

Abstract: Author post-print (accepted) deposited by Coventry University's Repository 'Machine learning in recycling business: an investigation of its practicality, benefits and future trends',

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Finally, evidence in support of this position can be found in the work of Panichayakorn and Jermsittiparsert (2019), Zhu et al (2017) and Ni et al (2021), who confirmed that AI and ML can mediate the role of supply chain agility and process improvements. Especially at COVID-19 times, the need of AI and ML-based deep intelligence are seemed to be paramount important to be able to deeply understand the dynamics of demand fluctuation and supply disruption (Di Vaio et al , 2020).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Finally, evidence in support of this position can be found in the work of Panichayakorn and Jermsittiparsert (2019), Zhu et al (2017) and Ni et al (2021), who confirmed that AI and ML can mediate the role of supply chain agility and process improvements. Especially at COVID-19 times, the need of AI and ML-based deep intelligence are seemed to be paramount important to be able to deeply understand the dynamics of demand fluctuation and supply disruption (Di Vaio et al , 2020).…”
Section: Discussionmentioning
confidence: 85%
“…The 15 ML-related publications reported miscellaneous findings, Tables 8 and 9 below summarize the articles and other publications findings, respectively while the discussion section thoroughly elaborates on the same. Most of the ML research specifically focused on demand forecasting, possible back-order prediction and deep learning aspects of demand variability (Abbas et al , 2020; Ni et al , 2021). Risk management, Automated Design and Manufacturing, Supply-Chain Quality Inspection at other areas of ML application among the wider theme of SCM research as our research indicated in Table 9.…”
Section: Methodsmentioning
confidence: 99%
“…Though ML models are successful in predicting PCR polymer characteristics such as the classification of recycled materials, recycling volume, recycling processing time, and so on, researchers are still unable to predict the properties of PCR polymers. 160 It is implicitly believed that coupling the experiences and perspectives of researchers in the PCR material stream with ML skills and approaches should be able to drive future breakthroughs in predicting the properties of PCR polymers. There is a large research space is out there for further exploration of PCR polymer property predictions using ML models.…”
Section: Discussionmentioning
confidence: 99%
“…In traditional target detection algorithms, the target region selection serves to find the region in the input image where the target may appear and get the location of the target to be measured. The sliding window method of selective search is often used, using rectangular boxes of different sizes and aspect ratios, sliding from left to right and from top to bottom to traverse the entire image [18]. Using this exhaustive approach generates a lot of useless and redundant information and is computationally intensive and poorly robust, greatly reducing the speed of the next step of feature extraction and classification.…”
Section: Intelligent Classification and Recyclingmentioning
confidence: 99%